Validation of a Novel Low-Cost Glaucoma Risk Calculator for Community-Based Screening in High-Risk Populations - Grimes K; Madu CT; Carrington C; Laroche D (Clinical Ophthalmology)
Kara Grimes,1,* Chisom T Madu,2 Carena Carrington,3 Daniel Laroche4,5,* 1School of Medicine, New York Medical College, Valhalla, NY, USA; 2School of Medicine, City University of New York School of Medicine, New Yorkṭ, NY, USA; 3School of Medicine, SUNY Downstate Health Sciences University, Brooklyn, NY, USA; 4Department of Ophthalmology, New York Eye and Ear Infirmary of Mount Sinai, New York, NY, USA; 5Advanced Eye Care of New York, New York, NY, USA*These authors contributed equally to this workCorrespondence: Daniel Laroche, Advanced Eye Care of New York, 49 West 127th Street, New York, NY, 10027, USA, Tel +1-212-663-0473, Email dlarochemd@aol.comPurpose: To assess the validity of a novel, low-cost glaucoma screening calculator in determining glaucoma risk in high-risk New York communities.Patients and Methods: This prognostic community-based study was conducted in New York City neighborhoods from 2022 to 2024 among participants aged 40 years and older. Glaucoma screenings were held at community gatherings including local fairs, senior citizen homes, places of worship, and in the lobby of medical offices. The screenings were conducted by trained non-physician medical personnel comprised medical students and medical assistants working under physician supervision. Participants’ intraocular pressure (IOP) and central corneal thickness (CCT) were measured in both eyes with a handheld tonometer and pachymeter, respectively. Participants then completed a comprehensive eye exam by an ophthalmologist to confirm glaucoma status. Statistical analysis was completed using MedCalc version 22.023 (MedCalc Software Ltd. Ostend, Belgium) with 95% confidence intervals.Results: Of the 823 study participants, 716 (mean age 62.9 ± 11.9 years) were eligible to participate and completed the comprehensive follow-up exam. 68% identified as Black, 6.7% identified as Hispanic/Latino, and 52.5% identified as female. The Laroche glaucoma calculator had a sensitivity of 93.5% (CI 89.1– 96.5%), specificity of 91.3% (CI 88.5– 93.6%), positive predictive value of 80.5% (CI 75.7– 84.6%), negative predictive value of 97.3% (CI 95.5– 98.4%) and accuracy of 91.9% (CI 89.6– 93.8%).Conclusion: The Laroche glaucoma calculator shows high sensitivity, specificity, positive predictive value, negative predictive value, and accuracy using affordable screening methods to determine glaucoma risk.Keywords: glaucoma risk calculator, affordable glaucoma screening, glaucoma screening tools, community-based glaucoma study, Laroche glaucoma calculator, eye screening